2014
DOI: 10.25077/jka.v3i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Profil Sindrom Stevens Johnson pada Pasien Rawat Inap di RSUP Dr. M. Djamil Padang Periode Januari 2010 sampai Desember 2011

Abstract: AbstrakSindrom Stevens Johnson (SSJ) merupakan reaksi mukokutaneus akut yang mengancam jiwa berupa nekrosis yang ekstensif dan lepasnya epidermis. Sindrom ini mengenai kulit, selaput lendir orifisium, dan mata dengan keadaan umum bervariasi dari ringan sampai berat. Meskipun kasusnya jarang terjadi, SSJ memiliki dampak yang signifikan terhadap kesehatan masyarakat karena angka morbiditas dan mortalitas yang tinggi. Tujuan penelitian ini adalah untuk mengetahui beberapa aspek kasus SSJ pasien rawat inap di RSUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another research showed that the incidence rate of SJS is 5 cases per million person per year and TEN is 2 cases per million person per year [3]. A similar study conducted in Indonesia reported that there are 35 SJS cases and 3 TEN cases in Dr. Mohammad Hoesin Central General Hospital Palembang from 2006-2008 and 22 SJS cases in Dr. M. Djamil Central General Hospital Padang from 2010-2011 [4,5]. SJS and TEN are rare cases, but the mortality rate is high, ranging from 25-70% and found higher in older age (>50 years) due to several factors such as comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Another research showed that the incidence rate of SJS is 5 cases per million person per year and TEN is 2 cases per million person per year [3]. A similar study conducted in Indonesia reported that there are 35 SJS cases and 3 TEN cases in Dr. Mohammad Hoesin Central General Hospital Palembang from 2006-2008 and 22 SJS cases in Dr. M. Djamil Central General Hospital Padang from 2010-2011 [4,5]. SJS and TEN are rare cases, but the mortality rate is high, ranging from 25-70% and found higher in older age (>50 years) due to several factors such as comorbidity.…”
Section: Introductionmentioning
confidence: 99%